Check Only Once? Health Information Exchange between Competing Private Hospitals. (February 2022) - Niu, Baozhuang; Xu, Haotao; Dai, Zhipeng
Highlights: We investigate competing hospitals' incentives of health information exchange to improve their decision-making coordination. We develop a two-period model where hospitals make one-shot service quality and two-period service price decisions. Hospitals' profit and social responsibility objectives are considered. Health information exchange is possible when hospitals' profit loss in health check fee is significant and their competition is intensified. Abstract: Health check is essential in medical diagnostic procedures, so double-check becomes common if patients have physical examination/blood tests in one hospital but transfer to another hospital in the next period. To save patients' costs, blockchain-based health information exchange for differentiated service is advocated but competing hospitals usually have incentive conflicts, especially those private hospitals who are most concerned with profitability. In this paper, we develop a two-period model where two private hospitals compete in both service quality and service charges. We formulate their tradeoffs towards health information exchange and find that interestingly, the two hospitals achieve incentive alignment when their profit loss in health check fee is significant and the service competition is intensified. We identify two driving forces, namely, the quality improvement effect and the price compensation effect, to interpret the rationality of the hospitals' preferences of health information exchange.